High BMI and Insulin Resistance Are Risk Factors for Spontaneous Abortion in Patients With Polycystic Ovary Syndrome Undergoing Assisted Reproductive Treatment: A Systematic Review and Meta-Analysis - Sun, Yi-Fei; Zhang, Jie; Xu, Yue-Ming; Cao, Zi-Yu; Wang, Yi-Zhuo; Hao, Gui-Min; Gao, Bu-Lang (Frontiers in Endocrinology, 2020)
Background：The risk of spontaneous abortion in patients with polycystic ovary syndrome (PCOS) undergoing assisted reproductive treatment (ART) is higher than that in patients without PCOS, however, no definitive risk factors have been confirmed to associate with the high spontaneous abortion rate in PCOS patients undergoing ART. This study was performed to assess the impact of relevant risk factors on spontaneous abortion in patients with PCOS. Clinical questions were formulated and organized according to the PICOS principle. Methods: A systematic review and meta-analysis were conducted on all published studies on PCOS and spontaneous abortion in Embase, PubMed, Web of Science and Cochrane Library. Related risk factors included body mass index (BMI), age, insulin resistance (IR), hyperandrogenism, and chromosome aberrations. All patients were diagnosed as PCOS using the Rotterdam criteria. The primary endpoint was miscarriage and live birth rate. Fixed-effect models were used to analyze homogeneous data, and subgroup and sensitivity analyses were performed on heterogeneous data. The source of heterogeneity was evaluated, and the random effect model was used to summarize the heterogeneity. Results: Among 1836 retrieved articles, 22 were eligible and included in the analysis with 11182 patients. High BMI (OR = 1.48, 95% CI [1.32, 1.67], MD = 1.35, 95% CI [0.58,2.12]) and insulin resistance (MD = 0.32, 95% CI [0.15, 0.49]) were associated with an increased risk of spontaneous abortion in PCOS patients undergoing ART. Older age (OR = 0.29, 95% CI [ 0.29, 0.44]，MD = 2.01, 95% CI [0.04, 4.18]), embryonic chromosomal aberrations (OR=0.75, 95%CI [0.31,1.77]), and hyperandrogenism (MD = 0.10, 95% CI [- 0.02, 0.22]) were not associated with the high spontaneous abortion rate in patients with PCOS. A subgroup analysis of BMI showed that there was no statistically significant difference in the effect between overweight and obesity on spontaneous abortion in PCOS patients undergoing ART (OR = 1.34, 95% [0.97, 1.85]). Conclusion: High BMI and insulin resistance are two risk factors for an increased risk of spontaneous abortion in PCOS patients undergoing ART, and losing weight and mitigating insulin resistance may decrease the spontaneous abortion rate in these patients undergoing ART.